Differences in Cholesterol Test Results Between POCT (Point of Care Testing) and Photometer Methods - Suparyati; Adelia Citra Anggraini (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Cholesterol is one of the components of fat or lipids that is essential for the body, in addition to carbohydrates, proteins, vitamins, and minerals. Cholesterol testing in the laboratory can be performed using two types of methods, namely automatic technique testing (POCT) and simple technique testing (photometer). This study aims to determine the difference in cholesterol test results using the POCT method and the photometer method. Method: This study is analytical in nature, using 30 venous blood samples from outpatients at Kraton Pekalongan Regional General Hospital. The examination was conducted using the POCT method with a photometer. The data were analyzed using normality tests and Wilcoxon tests using SPSS. Result: The average cholesterol test result using the POCT method was 173.37 mg/dl, while the photometer method yielded a result of 127.77 mg/dl. The statistical test results showed (sig value = 0.000 < 0.05), indicating a significant difference between the two methods. Conclusion: There is a significant difference between the cholesterol results obtained by the POCT method and the photometer.